Social Justice, Media and Technology in Teacher Education 27th ATEE Spring Conference, ATEE 2021, Florence, Italy, October 28-29, 2021, Revised Selected Papers - Ranieri, Maria; Pellegrini, Marta; Menichetti, Laura; Roffi, Alice; Luzzi, Damiana (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book constitutes the refereed proceedings of the 27th ATEE Spring Conference on Social Justice, Media and Technology, ATEE 2021, held in Florence, Italy, during October 28-30, 2021. The 19 full papers included in this book were carefully reviewed and selected from 49 submissions. They were organized in topical sections as follows: teaching critical media/digital literacy in multicultural societies; decommodifying teacher (digital) education; and digital technology and equity for inclusive teaching.
Teaching critical media/digital literacy in multicultural societies -- Media Education and Digital Storytelling: an Experience of University Teaching -- Engaging with Media Constructs and Power Dimensions in Initial Teacher Education: Enabling Student Teachers to Challenge Stereotypical Representations of Minorities in the Classroom -- Immersive Environments in Higher Education: the Digital Well-Being Perspective -- Cultures, Intersections, Networks. The Role of Algorithms in Defining Power Relations Based on Gender, Race, Class, Disability -- Integration of LifeComp and DigComp 2.2 as a Theoretical Framework for Media Education -- Digital Citizenship Education Curriculum. Results of a National Investigation and Didactic Proposals -- Study and Analysis on the Student Response System Adoption: Experimentation in a Programming Course -- Decommodifying teacher (digital) education -- Learning Analytics to Foster Quality Culture in Education and Training Organizations -- Legalisation Issues and Reconfiguration of Education? Challenges for Nordic Teacher Education in the Digital Age -- The Training of Teachers in Citizenship Education through Theatre and Dialectical Method -- Educating Students at Teacher Education Faculties in Art Fields (Visual Arts and Music) in the Online Environment -- Digital technology and equity for inclusive teaching -- "La scuola si Nutre del Territorio nel Quale Alberga" "The school is Nourished by the Local Context" -- Teaching in Upper Secondary Schools with High Migratory Complexity: the European Project QuaMMELOT -- Accessible School Textbooks for Students with Hearing Impairments -- Educational Robotics for Inclusive Design -- Teachers in a Searchable World: Findings from an Introductory Survey -- Teaching with Digital Conceptual Maps for the Development of Inclusive Processes -- Teacher Professional Development on Social Inclusion: the PLEIADE Approach -- Educational Technologies, Social and Emotional Learning and School Inclusion: Challenges and Opportunities.
Keywords: Teachers-Training of; Application software; User interfaces (Computer systems).; Human-computer interaction; Education-Data processing; Social sciences-Data processing; Teaching and Teacher Education; Computer and Information Systems Applications; User Interfaces and Human Computer Interaction; Computers and Education; Computer Application in Social and Behavioral Sciences